Sparse channel estimation for OFDM system weighted lp norm - Jian-bin FU; Hua PENG; Zheng DONG (Tongxin xuebao)
The new lp norm was introduced to substitute the l0 and l1 norm,as they met some problems when used to estimate sparse channel in LMS algorithm.By analyzing the lp norm,the optimal value of p was obtained,it was 1/2.Then a most sparse solution could be gotten for channel estimation.And it both saved the cost for training sequence and solved the lack of data size by using data reusing method.Simulation results show that the lp-LMS performs better than the existing methods,combining with data reusing when the training sequence is certain short.